Cambodia : Sustaining Strong Growth for the Benefit of All - World Bank Group (World Bank, Washington, DC, 2017)
Cambodia has become one of the world’s leaders in poverty reduction and shared prosperity. Cambodia sustained an average growth rate of 7.6 percent in 1994-2015, ranking sixth in the world, and has now become a lower middle-income economy. Cambodia’s success has ridden on employment creation, although labor productivity gains have been lower than in other fast-growing economies, partly due to lower capital intensity. Growth has also been driven to a large extent by the country’s rich and diverse natural capital which supports the livelihoods of millions of Cambodians. Going forward, Cambodia may not be able to rely on the same factors that drove strong growth and poverty reduction over the past two decades. Declining external competitiveness threatens the sustainability of garments and tourism and poses a challenge to economic diversification and moving up the value chain. A number of institutional, human capital, and, to a lesser extent, infrastructure constraints hamper competitiveness as well as the creation of a vibrant private sector in Cambodia. In light of these challenges and risks, areas of development for ensuring strong, inclusive, and sustainable growth with shared prosperity in Cambodia going forward were identified, based on analysis and consultations with stakeholders. The areas for development were ranked based on the impact interventions will have on maintaining strong and sustainable growth and achieving poverty reduction and shared prosperity, in terms of creating and enhancing households’ participation in better economic opportunities, the share of the population affected, and complementarity with other interventions.